Nursing Students Interests to Work Overseas: A Mixed Methods Study - Pepin Nahariani (Journal of Global Pharma Technology, 2016)
Introduction: Opportunities for nurses to work abroad are extensive. But in-fact 60% of nurses work in the country, 35% work outside of their competence and only 5% work abroad. The study aimed to analyze the interest of nursing students to work overseas. Methods: a mixed-methods design was conducted. The totals samples were 395 respondents of Diploma Nursing, Bachelor of Nursing, and Profession of Ners programs. The sample was taken using totals sampling. The data collection was taken by a nursing migration questionnaire, a statistical test using linear logistic regression. The qualitative approach used by an in-depth interview. Eight Participants who were from the Bachelor of Nursing students. Results: The results showed that almost 62.5% (247) of respondents indicated an intention to work overseas. Whereas the most significant influence of a plan to work abroad was gender, 43% of females, the academic of nursing bachelor programs were 49%, English language skills were 29%, and income is less than 3 million 61%. The country chosen had the highest probability (OR 3.5), thus the planned future overseas (OR 1.47), the information (OR 1.26), and the study program (OR 1.25). But the lower grades of intention working abroad were income (OR 0.6). Conclusion: Based on this research showed that most students interest in working abroad in Kuwait (83.5%), Japan (15.7%) dan Arab Saudi (0.3%). Besides, the few students’ interests work in another country that has a foreign language from English. The implementation of increasing career paths and improving the quality of human resources through foreign language skills will provide excellent opportunities to work overseas.Keywords: Student; Nursing; Interest; Intention; Working overseas.